Word Cards Design as Learning Media for Dyslexia Students in Elementary School - Haifa, Nisrina; Respati, Resa; Chairunnisaa, Chairunnisaa (Journal of Education for Sustainability and Diversity, 2022)
Reading is one of the most important activities in elementary school to get necessary knowledge and skills. Each students have different reading capability, especially dyslexic students whom known for their hardship in terms of reading capability. This will certainly have an impact on the growth of those students. One of the solutions for the problems are the usage of learning tools, to help them navigate throughout their school life. Media that are used should be easy and fun to use to keep them engaged, but still provide necessary knowledge for dyslexic students understand and remember each letter in alphabetical sequence. This research wants to provide solution about learning media in the form of word cards. The method used is research and development with observation techniques, interviews and documentation are conducted to discover problems and learning media needed for dyslexic students in the field, as well as to develop learning media for expert validation. It is expected that this word cards design as a learning media can be developed according to the needs of dyslexic students in elementary schools to assist in the reading process.